RANCANG BANGUN DESALINASI SURYA TIPE SINGLE BASIN DOUBLE SLOPE DI SELAT PANJANG KOTA-RIAU - Awaludin Martin; Benny Wahyudi; Fikri Fahlevi Nasution (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
People in coastal areas must buy or use rainwater to get clean water, but the availability of clean water itself still depends on the availability of nature where when the dry season comes it is very difficult to get clean water. The solution to this problem is to utilize seawater through a seawater purification process (desalination) by removing excess salt content in the water by utilizing solar energy. The aims of this study are to design, manufacture, and test solar desalination with a single basin double slope type with the addition of an internal reflector and a wick in the form of a sponge. Where the test was carried out in Selat Panjang Kota, Meranti Islands Regency, Riau Province, Indonesia (1Â° North Latitude and 102.70Â° East Longitude). This study resulted in the highest efficiency found in the test with a sponge pore dimension of 0.20 mm compared to a sponge pore dimension of 0.35 mm and 0.50 mm. With the average intensity of solar radiation on that day of 733,079 W/m2, the desalination water produced was 3,380 kg and the efficiency was 27.05%. The quality of the desalinated water shows that all test parameters have values below the drinking water standard, which is given by the Minister of Health Regulation NUMBER 492/MENKES/PER/IV/2010. This indicates that desalinated water is suitable for drinking as well.